Reproductive potential of silver European eels (Anguilla anguilla) migrating from Vistonis Lake (Northern Aegean Sea, Greece) - MACNAMARA, R.; KOUTRAKIS, E. T.; SAPOUNIDIS, A.; LACHOUVARIS, D.; ARAPOGLOU, F.; PANORA, D.; McCARTHY, K. T. (Mediterranean Marine Science, 2014)
The European eel (Anguilla anguilla), once abundant throughout much of Europe and North Africa, has recently been classified as critically endangered. Information on its biology from the eastern Mediterranean is lacking, especially in relation to spawner quality. Therefore, silver eels were sampled during their seaward spawning migration from Vistonis Lake in Greece. Characteristics linked to reproductive output and success (i.e. body size and condition, sex ratio, silvering, Anguillicola crassus infection, fecundity and oocyte diameter) were examined. The lake produced large (687–1138 mm), exclusively female silver eels, 61.7% of which were infected by A. crassus. Silver eel fecundity, the first estimates from the southern part of the species range, was positively related to body length (R2 = 0.693; P < 0.001) and body weight (R2 = 0.731; P < 0.001). Fecundity did not differ between A. crassus infected and uninfected silver eels, but Greek silver eels were significantly more fecund than those in north-west Europe. The reproductive potential of Vistonis Lake silver eels and their contribution to the A. anguilla spawning stock is discussed.